2012
DOI: 10.1377/hlthaff.2011.0729
|View full text |Cite
|
Sign up to set email alerts
|

Among Dual Eligibles, Identifying The Highest-Cost Individuals Could Help In Crafting More Targeted And Effective Responses

Abstract: The nearly nine million people who receive Medicare and Medicaid benefits, known as dual eligibles, constitute one of the nation's most vulnerable and costly populations. Several initiatives authorized by the Affordable Care Act are intended to improve the health care delivered to dual eligibles and, at the same time, to achieve greater control of spending growth for the two government programs. We examined the 2007 costs and service use associated with dual eligibles. Although the population is indeed costly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…Our study also showed that younger age was the most important independent predictor of Medicare spending. This is consistent with the fact that younger patients with CLD who qualify for Medicare can only be enrolled due to their disability or other chronic condition such as ESRD 17 18. Furthermore, we expect that the rate of patients with HCV will continue to increase as a result of the CDC's current guidelines which recommend screening all patients between the ages of 45 and 65 regardless of risk factors for HCV 19.…”
Section: Discussionsupporting
confidence: 72%
“…Our study also showed that younger age was the most important independent predictor of Medicare spending. This is consistent with the fact that younger patients with CLD who qualify for Medicare can only be enrolled due to their disability or other chronic condition such as ESRD 17 18. Furthermore, we expect that the rate of patients with HCV will continue to increase as a result of the CDC's current guidelines which recommend screening all patients between the ages of 45 and 65 regardless of risk factors for HCV 19.…”
Section: Discussionsupporting
confidence: 72%
“…1 In particular, MMEs were much more likely to have depression, Alzheimer's disease, diabetes, heart failure, chronic kidney disease, chronic obstructive pulmonary disease (COPD), asthma, or stroke. They account for a disproportionate share of Medicare spending (Coughlin, Waidmann, & Phadera, 2012 (Segal, 2011). This study updates those findings with 2007 to 2009 data, and examines differences in potentially avoidable hospitalization rates by setting, state, and medical condition.…”
Section: Introductionmentioning
confidence: 68%
“…Care coordination is especially challenging when complex care requires payment from Medicare for medical (acute) services and from Medicaid for long-term services and supports. 9–11 The most widespread new payment models, such as Medicare contracts with accountable care organizations and patient-centered medical homes, have primarily addressed Medicare utilization. But new programs, such as state participation in the Financial Alignment Intiative and Medicare Advantage Special Needs Plans of the Centers for Medicare and Medicaid Services (CMS), are integrating acute and long-term care payment and delivery systems.…”
mentioning
confidence: 99%